How The Secret Changed My Life : Real People, Real Stories - Byrne, Rhonda (London Simon & Schuster, 2016)
Since the very first publication of The Secret a decade ago, Rhonda Byrne's bestselling book has brought forth an explosion of real people sharing real stories of how their real lives have miraculously changed for the better. How The Secret Changed My Life presents a selection of the most heartwarming and moving stories in one inspirational volume. Each story provides an authentic, real-life illustration of the pathway that leads to success in every area of life: money, health, relationships, love, family, and career.
Keywords: New Thought -- Self-actualization (Psychology) -- Success--Psychological aspects